2018
DOI: 10.1186/s12909-018-1119-0
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and well-being of university nursing students in Hong Kong: a cross-sectional study

Abstract: BackgroundUniversity nursing students experience higher levels of academic stress than those of other disciplines. Academic stress leads to psychological distress and has detrimental effects on well-being. The ability to overcome such adversity and learn to be stronger from the experience is regarded as resilience. Resilience is found to have an impact on learning experience, academic performance, course completion and, in the longer term, professional practice. Resilience and positive coping strategies can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 40 publications
16
112
2
11
Order By: Relevance
“…The resilience score in our study, 29.71, was higher than most other studies which involved a nursing population and used the CD‐RISC‐10. Chow et al () reported a resilience score of 24.0 with Hong Kong university nursing students. Ang et al () found a resilience score of 25.9 in their study with Singapore nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resilience score in our study, 29.71, was higher than most other studies which involved a nursing population and used the CD‐RISC‐10. Chow et al () reported a resilience score of 24.0 with Hong Kong university nursing students. Ang et al () found a resilience score of 25.9 in their study with Singapore nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Items were measured on a Likert scale: “not true at all,” “rarely true,” “sometimes true,” “often true” and “true nearly all the time.” Respondents were asked how much they agreed with each item (e.g., “I can deal with whatever comes my way”) as it applied over the last month. The CD‐RISC‐10 has been used among nursing students in Nigeria (Aloba, Olabisi, & Aloba, ) and Hong Kong (Chow et al, ) and with practising nurses in Singapore (Ang et al, ). CD‐RISC‐10 scores range from 0 to 40 (higher scores indicating elevated resilience).…”
Section: Methodsmentioning
confidence: 99%
“…This perspective defined the concept of psychological well-being (PWB), which is the focus in this study. Most of the previous studies about these two constructs have focused much on medical (Bigdeli, Najafy & Rostami, 2013;Souri & Hasanirad, 2011) and nursing (Abiola, Olorukooba & Afolayan, 2017;Chow et al, 2018;Jin & Kim, 2017) students, based on the assumption that these groups are faced with more challenges. All of these studies found that resilience has a moderate to strong and positive relationship with PWB.…”
Section: Resilience and Psychological Well-beingmentioning
confidence: 99%
“…According to He et al, in coping with these stressors, the predictors of psychological well‐being among undergraduate nursing students include internal factors such as self‐efficacy, resilience, and mindfulness, as well as external factors such as social support. Some studies focusing on psychological well‐being have reported that well‐being is associated with resilience, self‐esteem, behavioral and affect‐focused strategies, family cohesion and social support …”
Section: Introductionmentioning
confidence: 99%
“…Some studies focusing on psychological well-being have reported that well-being is associated with resilience, self-esteem, behavioral and affect-focused strategies, family cohesion and social support. [9][10][11] Ratanasiripong and Wang, 7 in their study assessed students' wellbeing using the Rosenberg self-esteem scale, the Center for Epidemiology Studies-Depression Scale Satisfaction with Life Scale, and the Revised Cheek and Buss Shyness Scale. They found that compared with students who were recruited from a comprehensive college with degree programs in education, arts, sciences, technology, and management, nursing students had higher levels of self-esteem and life satisfaction and that they reported lower levels of depression and social difficulties.…”
Section: Introductionmentioning
confidence: 99%